Extracción, identificación y prueba microbiológica del agar extraído de Gracilaria fortissima dawson (rhodophyta, gigartinales, gracilariaceae) (ING) - Sánchez, M.V. (2008)
The red seaweed Gracilaria fortissima colected in the caribean coast of Costa Rica, was studied for the extraction, identification and microbiological performance of the agar contend of this plant, as well as the mineral contend. The research was done focused on the agar quality included pH, % extraction, geling point, fusion point and gel strength, as well as infrared analysis and the performance as a microbiological culture of bacteria and fungus and compared with commercial agar from BDH chemicals.